Osteomyelitis and pyomyositis due to Staphylococcus aureus in an osteomalacic adult with multiple fractures - Masumi Ogawa; Takatoshi Kitazawa; Yusuke Yoshino; Koji Morita; Toshio Ishikawa; Yasuo Ota (Greater Baltimore Medical Center, 2021)
Multifocal osteomyelitis and pyomyositis usually arise from hematogenous dissemination, especially in patients with immunodeficiency, trauma, or injection drug abuse. We report the case of a 75-year-old man with multifocal pyomyositis and osteomyelitis, which were due to Staphylococcus aureus and were presumably related to multiple fractures. The patient had no risk factors for these hematogenous infections. He was treated with antibiotic therapy for about 80 days and drainage of the abscesses. Regarding the cause of his multipe fractures, he was found to have hypophosphatemia and eventually diagnosed as osteomalacia. To our best knowledge, this case was the first report on multifocal osteomyelitis and pyomyositis around the fracture sites in an osteomalacic adult. Osteomalacia should be considered as one of the differential diagnoses when osteoarticular infection with multifocal fractures is detected.